2022
DOI: 10.3390/toxics10100590
|View full text |Cite
|
Sign up to set email alerts
|

Selected Biochemical Markers Change after Oral Administration of Pesticide Mixtures in Honey Bees

Abstract: The honey bee is an important pollinator. In the environment, it can be exposed to many harmful factors, such as pesticides. Nowadays, attention is paid to evaluating the potentially harmful effects of these substances. This study aimed to evaluate the effect of worst-case environmental concentrations of pesticide mixtures on honey bee survival and selected physiological markers (the activity of ALT, AST, ALP, and GGTP, and the concentration of albumin, creatinine, urea, and uric acid). Pesticides of three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In the literature, there are no data on the effect of acetamiprid at this dose on the analyzed indicators. At higher concentrations in an acute toxicity test (200,000 ppb), acetamiprid increased AST and ALT activities in the hemolymph [45]. This insecticide (600, 1200, 2400, 6000, and 60,000 ppb) also affected polyphenol oxidase, carboxylesterase, and the detoxification enzyme GST [46].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the literature, there are no data on the effect of acetamiprid at this dose on the analyzed indicators. At higher concentrations in an acute toxicity test (200,000 ppb), acetamiprid increased AST and ALT activities in the hemolymph [45]. This insecticide (600, 1200, 2400, 6000, and 60,000 ppb) also affected polyphenol oxidase, carboxylesterase, and the detoxification enzyme GST [46].…”
Section: Discussionmentioning
confidence: 92%
“…Glyphosate can affect honey bees' antioxidant levels and detoxification indicators, depending on the concentration, application method, and age of the bees [9,47]. AST, ALT, ALP, and GGTP activities did not change in the acute toxicity test (20,000,000 ppb) [45]. Using glyphosateadded syrup at concentrations of 0.1 and 1 ppb, Almasri et al observed changes in ALP activity in the intestinal tissue (usually an increase, but these changes were not statistically significant).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given the fact that the mean concentration of herbicides was much higher than that of fungicides in sick/dead bees (286 ng/g vs. 155 ng/g, Figure 2 ), the sick bees could be mostly attributed to exposure to herbicides. It is also likely that the death and sickness of bees could have been caused by the synergistic effect of mixtures of a variety of pesticides, with 1.74 pesticides detected from a sick/dead bee on average [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies investigating the relationships between bees and pesticides. It was found that insecticides are a lethal threat, whereas herbicides and fungicides could cause a variety of health effects on bees; synergistic effects are even observed when mixtures of various pesticides are applied [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Other studies demonstrate significant pesticide exposure for bees, indicating the prevalent use of pesticides, even though several bees’ main activity regions are not intended for pesticide use [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%